Ciguatoxin prevalence in 4 commercial fish species along an oceanic exposure gradient in the US Virgin Islands. (30th April 2018) - Loeffler, Christopher R.; Robertson, Alison; Flores Quintana, Harold A.; Silander, Miguel C.; Smith, Tyler B.; Olsen, David
Abstract: Ciguatera fish poisoning is a seafood‐toxin illness resulting from consumption of fish contaminated with ciguatoxins. Managing ciguatera fish poisoning is complex. It is made easier, however, by local fishers from endemic areas reporting regional predictability for local fish species' ciguatera fish poisoning risk, which the present study then tested. We investigated the prevalence of ciguatoxins in 4 commonly marketed and consumed species (Balistes vetula, Haemulon plumierii, Ocyurus chrysurus, and Epinephelus guttatus) across an oceanic gradient (north, south, east, and west) from the US Virgin Islands. Fish muscle extracts were analyzed for Caribbean ciguatoxins using an in vitro mouse neuroblastoma (N2a) cytotoxicity assay and confirmed by liquid chromatography–tandem mass spectrometry (LC‐MS/MS). Fish collected from the north location had 0 fish with detectable ciguatoxins; this site also had the greatest wave energy. Caribbean ciguatoxins in fish ranged from 0.01 to 0.11, 0.004 to 0.10, and 0.005 to 0.18 ng Caribbean ciguatoxin‐1 eq/g, from the west, east, and south respectively. Ciguatoxin‐like activity was detectable by the N2a assay in 40, 41, 50, and 70% of H. plumierii, O. chrysurus, B. vetula, and E. guttatus, respectively. Of the fish collected, 4% had Caribbean ciguatoxin levels exceeding the US Food and Drug Administration guidance of 0.1 ng Caribbean ciguatoxin‐1 eq/g fish. These findings concurred with spatial ciguatera fish poisoning prevalence information provided by local fishers in the US Virgin Islands and demonstrate how partnerships between researchers and fishers can aid the improvement of science‐based ciguatera fish poisoning management. Environ Toxicol Chem 2018;39:1852–1863. Published 2018 Wiley Periodicals Inc. on behalf of SETAC. This article is a US government work and, as such, is in the public domain in the United States of America.